Whole genome sequencing identifies circulating Beijing-lineage Mycobacterium tuberculosis strains in Guatemala and an associated urban outbreak. Issue 6 (December 2015) - Saelens, Joseph W.; Lau-Bonilla, Dalia; Moller, Anneliese; Medina, Narda; Guzmán, Brenda; Calderón, Maylena; Herrera, Raúl; Sisk, Dana M.; Xet-Mull, Ana M.; Stout, Jason E.; Arathoon, Eduardo; Samayoa, Blanca; et al.
Summary: Limited data are available regarding the molecular epidemiology of Mycobacterium tuberculosis ( Mtb ) strains circulating in Guatemala. Beijing-lineage Mtb strains have gained prevalence worldwide and are associated with increased virulence and drug resistance, but there have been only a few cases reported in Central America. Here we report the first whole genome sequencing of Central American Beijing-lineage strains of Mtb. We find that multiple Beijing-lineage strains, derived from independent founding events, are currently circulating in Guatemala, but overall still represent a relatively small proportion of disease burden. Finally, we identify a specific Beijing-lineage outbreak centered on a poor neighborhood in Guatemala City.